Social Implications and Sectarian Divisions: Analyzing Bid‘ah and Tawhid Within Salafi Teachings - A‘la, Abd; Bakar, Abu (Fakultas Ushuluddin dan Dakwah Institut Al Fithrah Surabaya, 2024)
This article examines the social implications of the Salafi understanding of bid‘ah as well as an analysis of bid‘ah in the Salafi teachings themselves. The Salafi movement often accuses Muslims outside their group of heresy, but the irony arises when their own doctrine of monotheism is the result of interpretations that are not explicitly found in the Quran and Sunnah. The Salafi concept of monotheism triggers excommunication and disbelief of other Islamic groups and deepens group fanaticism, which has a negative impact on the solidity and social cohesion of Muslims. Salafi Jami, for example, opposes Salafi Harakī or Surūrī, exposing fanaticism and divisions within Salafi itself. Using a descriptive-analytical approach, this study finds that unilateral truth claims and sectarian fanaticism within Salafi groups reinforce divisions and prolonged conflicts within the Muslim community. They also have heresy in the context of their tawhīd consisting of ulūhiyyah, rubūbiyyah, and al-asmā’ wa al-sifāt. This research underscores the importance of studying these groups’ interpretations within their social context and subjectivity. As a result, it is difficult for Salafi and other radical groups to unite solidly, and Muslims continue to face divergent views and prolonged conflict.